2020
DOI: 10.24875/gmm.20000478
|View full text |Cite
|
Sign up to set email alerts
|

Factores asociados a muerte en niños con COVID-19 en México

Abstract: Introducción: Se informa que la mayoría de los niños afectados por SARS-CoV-2 cursan asintomáticos y que en ellos la mortalidad por COVID-19 es baja; en México se desconoce la información al respecto en este grupo de la población. Objetivo: Evaluar los factores de riesgo asociados a mortalidad en niños mexicanos con

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
0
6
0
6
Order By: Relevance
“…The three prognostic models presented in this work analyze the effect that risk variables have in different scenarios, particularly in patients in ICU; the analysis of Ñamendys Silva is consistent (12), who analyzed the decision made by the health authorities in Mexico during the second wave of infections, in December 2020, when the number of beds with a ventilator increased by 4.7 times (from 2,446 to 11,634) in hospital areas not equipped with intensive care, consequently, mortality was 12% higher, probably explained by human resources and the equipment had a lower quality of care. A recently published analysis in the pediatric population demonstrated the relationship among age, the clinical presentation with intubation, and the need for intubation as the variables associated with mortality (27). Some limitations of this study include the following: (a) As each hospital center feeds the database and the results are issued as cases are added, reports on the outcomes are subject to the data being updated.…”
Section: Discussionmentioning
confidence: 99%
“…The three prognostic models presented in this work analyze the effect that risk variables have in different scenarios, particularly in patients in ICU; the analysis of Ñamendys Silva is consistent (12), who analyzed the decision made by the health authorities in Mexico during the second wave of infections, in December 2020, when the number of beds with a ventilator increased by 4.7 times (from 2,446 to 11,634) in hospital areas not equipped with intensive care, consequently, mortality was 12% higher, probably explained by human resources and the equipment had a lower quality of care. A recently published analysis in the pediatric population demonstrated the relationship among age, the clinical presentation with intubation, and the need for intubation as the variables associated with mortality (27). Some limitations of this study include the following: (a) As each hospital center feeds the database and the results are issued as cases are added, reports on the outcomes are subject to the data being updated.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is one of the most controversial risk factors. In a study of mortality of children with COVID-19 in Mexico, obesity was found not to be an associated risk factor 7 . In contrast, in a group of children hospitalized at a children's hospital in New York, 50% of which were Hispanic, obesity was the main comorbidity (22%) and was significantly associated with mechanical ventilation in children > 2 years of age (6 of 9 [67%] vs. 5 of 25 [20%]) 18 .…”
Section: Discussionmentioning
confidence: 93%
“…Pneumonia is a well-known risk factor for children with COVID-19 for both death and admission to intensive care 7 . One of the main risk factors for a bad prognosis is lung damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Señor Editor, Después de leer artículo de Rivas-Ruiz, et al 1 , percibimos ciertos errores y sugerimos su atención. La literatura evidencia que existen diferencias en el proceso de la enfermedad por coronavirus 2019 (COVID-19) entre los lactantes, niños y adolescentes dentro del grupo pediátrico como lo reportaron Panahi, et al 2 , donde los niños cursaban mayormente con fiebre y tos seca, mientras que los lactantes presentaron aumento de la frecuencia cardiaca.…”
unclassified